2023
DOI: 10.1136/ijgc-2023-004275
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) vaccination: a call for action in Italy

Abstract: Human papillomavirus (HPV) is the most common sexually transmitted infection. The implementation of primary prevention aims to reduce the burden of HPV infection and HPV-related disease. However, HPV-related diseases are still a concern, even in high-income countries. Approximately 570 000 new cervical cancer cases are diagnosed in Italy every year. Prophylactic HPV vaccines have been developed to minimize the spread of HPV. Growing evidence supports the administration of HPV vaccines (even just one dose) in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
(127 reference statements)
0
8
0
Order By: Relevance
“…Fourth, only a minority of patients included in this study received adjuvant vaccination. Although we are expecting a limited effect of HPV vaccination in this cluster of patients, growing evidence supports the adoption of vaccination after primary treatment (Bogani et al ., 2021a, 2023; Di Donato et al ., 2022). Even in our series, we observed that patients receiving vaccination were at a lower (but not statistically significant) risk of developing HSIL/CIN2+ recurrence in comparison to those who had not.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, only a minority of patients included in this study received adjuvant vaccination. Although we are expecting a limited effect of HPV vaccination in this cluster of patients, growing evidence supports the adoption of vaccination after primary treatment (Bogani et al ., 2021a, 2023; Di Donato et al ., 2022). Even in our series, we observed that patients receiving vaccination were at a lower (but not statistically significant) risk of developing HSIL/CIN2+ recurrence in comparison to those who had not.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of primary prevention aims to reduce the burden of HPV infection and HPV-related disease [ 89 ]. There are five approved HPV vaccines, three of them in Europe, which prophylactically prevent HPV infection, despite each of them targeting different strains [ 90 ].…”
Section: Vaccination Prophylaxis and Cancer Preventionmentioning
confidence: 99%
“…There are five approved HPV vaccines, three of them in Europe, which prophylactically prevent HPV infection, despite each of them targeting different strains [ 90 ]. With more than 200 million doses administered to date, HPV vaccines are considered to be safe and effective in preventing HPV-related infections and cancers [ 89 ]. Therefore, in 2020, the FDA in the United States and the EMA in Europe extended the use of HPV vaccines to males [ 91 ].…”
Section: Vaccination Prophylaxis and Cancer Preventionmentioning
confidence: 99%
“…Since the decade 2010-2019, several countries have extended vaccination to boys of the same age, and more will follow (42). Despite the availability of a vaccine, the percentage of HPV-vaccinated girls still varies significantly across countries, ranging from 99% in Malta to 3% in Bulgaria, according to the latest updated and has yet to be fully addressed (44,45). Despite the improvements achieved in the individual cohorts, the average HPV vaccination coverage rate in girls and boys is still far from the expected optimal threshold envisaged by the Italian national vaccination prevention plan (i.e., 95% at age 12), and there is an obvious problem of inequality between regions as recently highlighted (45,46).…”
Section: Vaccination Against Hpvmentioning
confidence: 99%